Inicjatywy opiekuńcze i oświatowo-wychowawcze łódzkiej społeczności żydowskiej w latach I wojny światowej – Przytulisko dla Dzieci Wyznania Mojżeszowego - Sosnowska, Joanna (Biuletyn Historii Wychowania, 2016)
In 1914–1918, the Łódź Jewish community organized activities for children and teenagers in more than ten social and charitable organizations and institutions. Some of them were established even before 1914, some were opened during WWI. The Shelter for Jewish Children was among the centres operating during the difficult war times and dating back to the time before the Great War. The Shelter was established on the initiative of Sara Poznańska, wife of Maurycy Poznański, a prominent Jewish industrialist and social activist in Łódź. Members of the Board of the new institution included rich, middle class Jewish women, factory owners and merchants. In 1917, they were joined by S. Poznańska as President, Maria Hertzowa as Vice-President, Stefania Hirszbergowa as Treasurer and Paweł Becker as Secretary of the Board. Several sections were identified in the Shelter with different functions in mind: the Pedagogical, Medical, Food, Maintenance, and Clothes Sections. The task of the Pedagogical section was care for the intellectual and physical development of the children. Efforts were made to propagate Polish issues in education (the children were taught history and the Polish language). The Medical Section focused on hygiene and the children’s health. The Food Section prepared hot meals, i.e. dinners and breakfasts. The Maintenance Section’s responsibility was to develop a sense of cleanliness and order in the children. The Clothes Section put an emphasis on maintaining the children’s clothes in order, mainly by mending them. During WWI, the Shelter took care of over 200 pre-school and school children (aged 4–12).